Functional Analysis of Rhythmic Jaw Movements Evoked by Electrical Stimulation of the Cortical Masticatory Area During Low Occlusal Loading in Growing Rats - Aung, Phyo Thura; Kato, Chiho; Abe, Yasunori; Ogawa, Takuya; Ishidori, Hideyuki; Fujita, Akiyo; Okihara, Hidemasa; Kokai, Satoshi; Ono, Takashi (Frontiers in Physiology, 2020)
The maturation of rhythmic jaw movements (RJMs) and related neuromuscular control has rarely been studied in animals, though this process is essential for regulating the development of stomatognathic functions. Previous studies have shown that occlusal hypofunction during growth alters masticatory performance. However, little is known about patterns of cortically-induced RJMs under conditions of soft-diet feeding during development. The aim of this study is to clarify the effect of low occlusal loading on the pattern of cortically induced RJMs and related neuromuscular responses in growing rats. Sixty-four 2-week-old male albino Wistar rats were randomly divided into two groups and fed on either a normal diet (control) or soft diet (experimental) soon after weaning. At 5, 7, 9 and 11 weeks of age, electromyographic (EMG) activity was recorded from the right masseter and anterior digastric muscles along with corresponding kinematic images in RJMs during repetitive intracortical microstimulation of the left cortical masticatory area (CMA). Rats in both groups showed an increase in gape size and lateral excursion until 9 weeks of age. The vertical jaw movement speed in both groups showed no significant difference between 5 and 7 weeks of age but increased with age from 9 to 11 weeks. Compared to the control group, the average gape size and vertical speed were significantly lower in the experimental group, and the pattern and rhythm of the jaw movement cycle were similar between both groups at each recording age. EMG recordings showed no age-related significant differences in onset latency, duration, and peak-to-peak amplitude. Moreover, we found significantly longer onset latency, smaller peak-to-peak amplitude, and greater drop-off mean and median frequencies in the experimental group than in the control group, while there was no significant difference in the duration between groups. These findings indicate that a lack of enough occlusal function in infancy impedes the development of patterns of RJMs and delays the neuromuscular response from specific stimulation of the CMA.